2023
DOI: 10.1038/s41392-023-01626-x
|View full text |Cite
|
Sign up to set email alerts
|

Human endogenous retroviruses as epigenetic therapeutic targets in TP53-mutated diffuse large B-cell lymphoma

Ying Fang,
Mu-Chen Zhang,
Yang He
et al.

Abstract: TP53 mutation (TP53mut) occurs in 10–20% of diffuse large B-cell lymphoma (DLBCL) cases and serves as an unfavorable biomarker of DLBCL progression. It confers resistance to immunochemotherapy, high-dose chemotherapy, autologous stem cell transplantation, and anti-CD19 chimeric antigen receptor T-cell therapy. Therapeutic targeting of TP53mut remains a significant challenge in DLBCL treatment. Here we assessed TP53mut in 667 patients with newly diagnosed DLBCL, including 576 patients treated with immunochemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In addition, uneven distribution among LME categories was observed for some common mutations and copy number alterations (CNAs), suggesting that the changes in the lymphoma microenvironment are primarily influenced by the genetic factors pertaining to the lymphoma cells themselves. This possibility is further supported by studies showing that specific genetic lesions that define or are over-represented in certain DLBCL genetic subtypes, such as mutations in TP53, NOTCH1, CREBBP, or NFKBIE, can induce changes in the composition or functionality of TME cells that characterize some of the LME categories [ 57 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. Such changes include low infiltration of CD4+ T cells and CD8+ T cells or reduced T-cell cytolytic activity due to immune exhaustion, which are features of the DP and IN category, respectively, and can contribute to the immune escape of the malignant B cells by disrupting T cell-mediated antitumor immune surveillance mechanisms.…”
Section: Current Molecular Classifications Of Dlbclmentioning
confidence: 93%
See 2 more Smart Citations
“…In addition, uneven distribution among LME categories was observed for some common mutations and copy number alterations (CNAs), suggesting that the changes in the lymphoma microenvironment are primarily influenced by the genetic factors pertaining to the lymphoma cells themselves. This possibility is further supported by studies showing that specific genetic lesions that define or are over-represented in certain DLBCL genetic subtypes, such as mutations in TP53, NOTCH1, CREBBP, or NFKBIE, can induce changes in the composition or functionality of TME cells that characterize some of the LME categories [ 57 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. Such changes include low infiltration of CD4+ T cells and CD8+ T cells or reduced T-cell cytolytic activity due to immune exhaustion, which are features of the DP and IN category, respectively, and can contribute to the immune escape of the malignant B cells by disrupting T cell-mediated antitumor immune surveillance mechanisms.…”
Section: Current Molecular Classifications Of Dlbclmentioning
confidence: 93%
“…To further investigate whether the identified overrepresented pathways could guide targeted therapy of the different genetic subtypes of DLBCL, R-CHOP was compared to R-CHOP in combination with a targeted agent in the genetic subtype-guided immunochemotherapy GUIDANCE-01 trial, where a simplified 20-gene algorithm was used to stratify patients in accordance with the classifier of Staudt et al [ 56 ]. The targeted agents included the histone deacetylase (HDAC) inhibitor tucidinostat, which was utilized for the EZB-like subtype because epigenetic alterations are a defining feature of the EZB-type tumors; ibrutinib, which was utilized for the BTK-dependent subtypes MCD-like and BN2-like; and the demethylating agent decitabine, which was utilized for the TP53-mutated subtype, based on its effect in counteracting the immune depletion of the microenvironment associated with TP53-mutated tumors [ 57 , 58 , 59 ]. Lastly, lenalidomide, an immunomodulatory drug, was utilized for the N1-like subtype and the unclassified patients based on the improved outcome of the lenalidomide + R-CHOP combination in two previous clinical trials of patients with DLBCL and because of the unavailability of a specific targeting agent for patients belonging to these genetic categories [ 60 , 61 ].…”
Section: Current Molecular Classifications Of Dlbclmentioning
confidence: 99%
See 1 more Smart Citation
“…The TP53 mutation serves as an adverse prognostic indicator in diffuse large B-cell lymphoma (DLBCL), conferring resistance to conventional therapies such as chemotherapy. Studies have demonstrated that TP53 mutation upregulates the H3K9 methyltransferase SUV39H1, leading to the inhibition of HERV expression via histone methylation [171,172]. Decitabine administration can counteract this mechanism, enhancing HERV expression, stimulating interferon release, and slowing down tumor advancement [172,173].…”
Section: Epigenetic Drugs For Cancer Treatmentmentioning
confidence: 99%
“…Studies have demonstrated that TP53 mutation upregulates the H3K9 methyltransferase SUV39H1, leading to the inhibition of HERV expression via histone methylation [171,172]. Decitabine administration can counteract this mechanism, enhancing HERV expression, stimulating interferon release, and slowing down tumor advancement [172,173]. Various approaches to combined drug administration are presented in Table 2.…”
Section: Epigenetic Drugs For Cancer Treatmentmentioning
confidence: 99%